A state-of-the-art overview of green bond markets: Evidence from technology empowered systematic literature review - Abhilash; Sandeep S. Shenoy; Dasharathraj K. Shetty (Cogent Economics & Finance, 2022)
Though the green bond markets are growing expeditiously, the summary overview of this market literature is sparse. This study addresses the gap by employing a bibliometric analysis through a systematic review of the literature approach and provides a state-of-the-art overview of the current trends, status, and future development of the green bond markets. To do so, the study reviewed 265 articles retrieved from the Scopus database spanning from 2011 to 2022. Akin to this, the study unpacks the publication trend, most influencing articles, prolific authors, top contributing journals, countries, as well as affiliations in green bond research. The review shows that the publication trend has surged exponentially with an annual growth rate of 55.12%. The study also reveals major themes such as sustainable development, sustainability, green bonds, sustainable finance, green finance, and sustainable investment. The findings of the study suggest curating future research with the main emphasis on multiple types of green bonds, the impact of various green projects, the attention of various market participants, and the incorporation of advanced technology for the development of the green bond market. The study will help policymakers, regulators, and academicians to promote sustainability.
Keywords: 330; bibliometric analysis; green bond; green projects; sustainable development; sustainable finance; systematic literature review